Lesing som anerkjennelse – den manglende dimensjonen i PISAs begrep om leseferdighet - Fauskevåg, Odin (Studier i Pædagogisk Filosofi, 2016)
This article discusses the PISA framework’s concept of reading. The main argument is that PISA’s cognitive approach to literacy only to a small extent captures the normative dimension of reading. Consequently, the test fails to reﬂect key aspects of literacy, such as identity, identity formation and the ability to participate in society on a deeper level. The argument is based on a normative or moral conception of meaning and reading comprehension, based on Hegel’s concept of recognition.